Synthesis, crystal structure and Hirshfeld surface analysis of a coordination compound of cadmium nitrate with 2-amino-benzoxazole - Razzoqova, Surayyo; Ruzimov, Yodgor; Toshov, Akobir; Torambetov, Batirbay; Ibragimov, Aziz; Ashurov, Jamshid; Kadirova, Shakhnoza (Acta Crystallographica Section E, Crystallographic Communications, 2025)
A coordination complex of cadmium nitrate [Cd(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2] with 2-amino-benzaxole (2AB; C<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">7H<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">6N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O), namely, tetra-kis-(2-amino-benzoxazole-κ<i style="box-sizing: inherit; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;">N <span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">1)bis-(nitrato-κ<i style="box-sizing: inherit; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;">O)cadmium(II), [Cd(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">4], has been synthesized from ethanol solutions of Cd(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2·H<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O and 2AB. The asymmetric unit comprises half a mol-ecule of [Cd(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">4], with the Cd<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II atom positioned on a twofold rotation axis. In the completed mol-ecular complex, four 2AB ligands and two nitrate anions each coordinate monodentately to the Cd<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II atom, leading to a distorted octa-hedral coordination environment. The crystal structure of [Cd(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2(2AB)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">4] exhibits several N-H⋯O inter-actions, resulting in the formation of a layered assembly parallel to (001). Hishfeld surface analysis was used to qu-antify the inter-molecular inter-actions.